(untitled) (Journal of the College of Basic Education, 2022)
Evolution has entered the joints of public life; We single out the political and administrative onesAs a result of the development that took place in the Arab society after Islam and the emergence of the caliphate institution afterthe death of the Messenger (PBUH) and the outskirts of the Arab-Islamic state following the conquests; From what cameIt led to the acquisition of many customs and traditions that were not prevalent in Arab societysimpleton; as a result of mixing with foreign people; Especially the Persian and Byzantine empiresWhich were characterized by splendor and luxury. It is only natural that you enter into the succession fees something ofChange . The titles and rings of the Umayyad caliphs were a share in that.